Designing UI/UX For SDN 1 Sukamulya Ciamis Website Using the Five Planes and WEBUSE Methodologies - Gumilah, Dena Surya; Rachman, Andi Nur; Aldya, Aldy Putra (Journal of Applied Information System and Informatic (JAISI), 2023)
The web-based information world is currently experiencing rapid growth, encompassing interactive, dynamic, and static elements, with educational institutions being one of its prominent users. It provides swift and precise information services, contributing significantly to the fundamental development of the education sector. The school profile website from the Ministry of Education and Culture (KEMENDIKBUD) currently only provides basic profile features. Due to the lack of information and features on the website, a redesign and further development are necessary. Therefore, this research, based on interviews with relevant parties such as SDN 1 Sukamulya, calls for a redesign and development of the website. The approach taken in this redesign and development utilizes the Five Plans method. The creation of a website that aligns with user preferences, combines an attractive design, and offers an experience that meets user needs. The design and development of this website will be evaluated using the WEBUSE method. WEBUSE (Web Usability Evaluation) is a method for assessing the extent of usability based on a comprehensive usability criteria questionnaire. In the UI/UX design phase, the Five Planes method was applied, and after the design phase, the website's feasibility was assessed using the WEBUSE method. This research successfully designed a website for SDN 1 Sukamulya by applying the Five Planes method in the design process. Based on the comparison of evaluations using the WEBUSE method, the usability score of the website improved from a usability score of 0.657, falling into the "good" range (0.6 - 0.8), to a usability score of 0.829, falling into the "excellent" range (0.8 - 1). This score indicates that the website's usability level is excellent, demonstrating that the design and development efforts have successfully provided an outstanding user experience.